2003
DOI: 10.1111/1540-627x.00079
|View full text |Cite
|
Sign up to set email alerts
|

Health and Female Self-Employment

Abstract: This study uses data from the Mature Women's Cohort of the National Longitudinal Survey of Labor Market Experience (NLSLME). The sample (n=1,412) comprises self‐employed, wage‐earning, and nonemployed women whose cumulative employment is measured by employment status between 1976 and 1995 and whose health status was measured in 1976 and in 1995. Three multivariate regression models, one for each type of employment status, are used to control for sociodemographic and for other factors thought to influence healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
2
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 11 publications
2
33
2
4
Order By: Relevance
“…As a potential consequence of the above-mentioned factors, the performance of their business does not fare as well as that of their male counterparts (Carter et al 2001). Some researchers also report poorer health of female entrepreneurs compared with male entrepreneurs or female employees (Arber and Lahelma 1993;Dolinsky and Caputo 2003). The current study found no gender-related differences between work-related behavior and experience patterns between female and male entrepreneurs.…”
Section: Discussioncontrasting
confidence: 48%
See 1 more Smart Citation
“…As a potential consequence of the above-mentioned factors, the performance of their business does not fare as well as that of their male counterparts (Carter et al 2001). Some researchers also report poorer health of female entrepreneurs compared with male entrepreneurs or female employees (Arber and Lahelma 1993;Dolinsky and Caputo 2003). The current study found no gender-related differences between work-related behavior and experience patterns between female and male entrepreneurs.…”
Section: Discussioncontrasting
confidence: 48%
“…While differences in the acquisition of start-up finances, professional networking, and risk taking have been described, no differences were reported for motivation and personal characteristics (Brindley 2005;Sexton and Bowman-Upton 1990). There is some evidence that the health of female entrepreneurs might be poorer than that of male entrepreneurs or female employees (Arber and Lahelma 1993;Dolinsky and Caputo 2003) but differences between countries have been described (Lahelma and Arber 1994). From a Finnish study, a lower cardiovascular risk score was reported for women compared with men across various occupations including entrepreneurs (Luoto et al 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Dolinsky and Caputo [16] find that among female workers, self-employed persons report worse subjective health than their wage-earning counterparts. Perry and Rosen [17] is particularly noteworthy.…”
Section: Relationship Between Self-employment and Healthmentioning
confidence: 99%
“…A study of 450 American entrepreneurs by Boyd and Gumpert (1983) found four sources of stress: 1) loneliness; 2) immersion in the business; 3) people problems; and 4) their need to achieve. It is also generally considered that there is an absence of research examining the potential negative health consequences of small firm ownership (Dolinsky & Caputo 2003). Boyd and Webb (1982), in examining the incidence of 'type A' personalities (thought to be linked to coronary heart disease) among a sample of small business owners, found that stress reduction programmes needed to be implemented for the majority of the sample.…”
Section: Assumption 3: Being Self-employed Will Be a Positive Work Exmentioning
confidence: 99%